2002
DOI: 10.1051/0004-6361:20011621
|View full text |Cite
|
Sign up to set email alerts
|

Study of electron density in planetary nebulae

Abstract: Abstract. We present a comparison of electron density estimates for planetary nebulae based on different emissionline ratios. We have considered the density indicators. The observational data were extracted from the literature. We have found systematic deviations from the density homogeneous models, in the sense that:We argue that the lower [O ii] density estimates are likely due to errors in the atomic parameters used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 48 publications
9
46
1
Order By: Relevance
“…On the other hand, a very different result was obtained by Meatheringham & Dopita (1991) Aller et al 1996;Feibelman et al 1994Feibelman et al , 1996Hyung 1994;Hyung & Aller 1995a,b, 1996, 1997a,b, 1998Hyung et al 1993Hyung et al , 1994aHyung et al ,b,c, 1995Hyung et al , 1997Hyung et al , 1999aHyung et al ,b, 2000Hyung et al , 2001Keyes et al 1990;Keenan et al 1993Keenan et al , 1996Keenan et al , 1997 they determined simultaneously electron densities and temperatures using a number of plasma diagnostic lines in the optical and ultraviolet and found that overall the data yielded compatible and consistent results. More recently, Copetti & Writzl (2002), using data published in the literature, compared the observed line ratios for a number of density-diagnostics, instead of densities deduced from them, thus avoiding discarding measurements that yield ratios close to or beyond the the low-or high-N e limits. They concluded that in general N e ([N i] Copetti & Writzl (2002) failed to find evidence in support of the result of McLaughlin & Bell (1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a very different result was obtained by Meatheringham & Dopita (1991) Aller et al 1996;Feibelman et al 1994Feibelman et al , 1996Hyung 1994;Hyung & Aller 1995a,b, 1996, 1997a,b, 1998Hyung et al 1993Hyung et al , 1994aHyung et al ,b,c, 1995Hyung et al , 1997Hyung et al , 1999aHyung et al ,b, 2000Hyung et al , 2001Keyes et al 1990;Keenan et al 1993Keenan et al , 1996Keenan et al , 1997 they determined simultaneously electron densities and temperatures using a number of plasma diagnostic lines in the optical and ultraviolet and found that overall the data yielded compatible and consistent results. More recently, Copetti & Writzl (2002), using data published in the literature, compared the observed line ratios for a number of density-diagnostics, instead of densities deduced from them, thus avoiding discarding measurements that yield ratios close to or beyond the the low-or high-N e limits. They concluded that in general N e ([N i] Copetti & Writzl (2002) failed to find evidence in support of the result of McLaughlin & Bell (1998).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Copetti & Writzl (2002), using data published in the literature, compared the observed line ratios for a number of density-diagnostics, instead of densities deduced from them, thus avoiding discarding measurements that yield ratios close to or beyond the the low-or high-N e limits. They concluded that in general N e ([N i] Copetti & Writzl (2002) failed to find evidence in support of the result of McLaughlin & Bell (1998).…”
Section: Introductionmentioning
confidence: 99%
“…A flag of warning must be raised, however, in regard to neutral species and ions with ionization potentials below that of hydrogen because their spectra could be affected by photo-excitation by continuum radiation. Such is the case of N i (Bautista 1999) that Copetti & Writzl (2002) tried to analyze on the same grounds as ionized species.…”
Section: Discussionmentioning
confidence: 99%
“…This result, if confirmed, would have a profound significant effect on nebular studies, especially N e determinations for low surface brightness H  regions which typically have very low electron densities. The extensive literature survey by Copetti & Writzl (2002) failed to find evidence in support of the result of McLaughlin & Bell (1998).…”
Section: Introductionmentioning
confidence: 97%
“…Using high resolution spectroscopic data obtained with an echelle spectrograph, mostly by the group led by Aller Aller et al 1996;Feibelman et al 1994Feibelman et al , 1996Hyung 1994;Hyung & Aller 1995a,b, 1996, 1997a,b, 1998Hyung et al 1993Hyung et al , 1994aHyung et al ,b,c, 1995Hyung et al , 1997Hyung et al , 1999aHyung et al ,b, 2000Hyung et al , 2001Keyes et al 1990;Keenan et al 1993Keenan et al , 1996Keenan et al , 1997 they determined simultaneously electron densities and temperatures using a number of plasma diagnostic lines in the optical and ultraviolet and found that overall the data yielded compatible and consistent results. More recently, Copetti & Writzl (2002), using data published in the literature, compared the observed line ratios for a number of density-diagnostics, instead of densities deduced from them, thus avoiding discarding measurements that yield ratios close to or beyond the the low-or high-N e limits. They concluded that in general N e ([N i] At low plasma densities, each collisional excitation by electron impact leads to the emission of a photon.…”
Section: Introductionmentioning
confidence: 99%